Psychometric Validation of a Malay Language Knowledge, Attitude, and Practice Scale for Food Handlers Using EFA and Rasch Analysis - Suriya Kumareswaran Vallasamy; Bala Murali Sundram (Asia Pacific Journal of Public Health, 2026)
Food- and water-borne diseases remain a significant public health concern, with food handlers playing a critical role in ensuring food safety. However, no validated knowledge, attitude, and practice (KAP) questionnaire in Malay language has been established. This study aimed to evaluate the psychometric properties of the Malay language version of the KAP questionnaire among Malaysian food handlers using exploratory factor analysis (EFA) and Rasch model analysis. A cross-sectional study was conducted among 298 food handlers in Johor, Malaysia, using convenience sampling. The instrument underwent translation, adaptation, and content validation prior to analysis. The data were suitable for factor analysis (Kaiser-Meyer-Olkin = 0.824; Bartlett’s P < .001). Exploratory factor analysis supported a 3-factor structure, and item refinement resulted in improved internal consistency (Cronbach α = .841-.942). Rasch analysis demonstrated acceptable dimensionality for attitude and practice, satisfactory item fit, and appropriate rating scale functioning. Person reliability ranged from 0.70 to 0.86, with acceptable separation indices, although slightly lower for knowledge. Acceptable differential item functioning (DIF) was observed across education level and work experience, with all DIF values remaining within the predefined acceptable thresholds. The Malay-language KAP questionnaire is therefore a valid and reliable tool for assessing food safety-related knowledge, attitudes, and practices of food handlers in Malaysia.